2015
DOI: 10.1016/j.automatica.2015.02.039
|View full text |Cite
|
Sign up to set email alerts
|

An approach to output-feedback MPC of stochastic linear discrete-time systems

Abstract: In this paper we propose an output-feedback Model Predictive Control (MPC) algorithm for linear discrete-time systems affected by a possibly unbounded additive noise and subject to probabilistic constraints. In case the noise distribution is unknown, the probabilistic constraints on the input and state variables are reformulated by means of the Chebyshev -Cantelli inequality. The recursive feasibility is guaranteed, the convergence of the state to a suitable neighbor of the origin is proved under mild assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 35 publications
0
97
0
Order By: Relevance
“…This can, however, potentially lead to a loss in control performance since the control policy u = v will not account for knowledge of future disturbances in the state prediction. To allow for handling hard input constraints in the presence of unbounded disturbances, the input constraints (2) can be relaxed in terms of expectation-type constraints [24] or chance constraints [9]. However, these approaches would not provide a rigorous guarantee for fulfillment of (2) with respect to all disturbance realizations.…”
Section: Saturation Of Stochastic Disturbances For Handling Hard Inpumentioning
confidence: 99%
See 3 more Smart Citations
“…This can, however, potentially lead to a loss in control performance since the control policy u = v will not account for knowledge of future disturbances in the state prediction. To allow for handling hard input constraints in the presence of unbounded disturbances, the input constraints (2) can be relaxed in terms of expectation-type constraints [24] or chance constraints [9]. However, these approaches would not provide a rigorous guarantee for fulfillment of (2) with respect to all disturbance realizations.…”
Section: Saturation Of Stochastic Disturbances For Handling Hard Inpumentioning
confidence: 99%
“…Less suboptimal 1 SMPC formulations entail online computation of both the feedback control gains and the open-loop control actions. Such formulations, however, lead to a nonconvex optimization [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, both the approaches are conservative, mainly because they (implicitly or explicitly) rely on worst-case techniques. If the uncertainties or the state and control disturbances are characterized as stochastic processes, the conservativeness of a deterministic worst case approach can be significantly reduced by the development of stochastic MPC algorithms with probabilistic state and/or input constraints (see [Farina et al, 2015] and the references therein reported).…”
Section: Introductionmentioning
confidence: 99%